Faculty development in point of care ultrasound for internists. Issue 1 (1st January 2016) - Maw, Anna; Jalali, Cathy; Jannat-Khah, Deanna; Gudi, Kirana; Logio, Lia; Evans, Arthur; Anderson, Stacy; Smith, Joshua
Abstract : Lack of general medicine faculty expertise is a likely contributor to the slow adoption of point of care ultrasound (POCUS) by internal medicine (IM) residency training programs. We developed a 10-week faculty development program, during which 15 faculty members participated in 2 hours and 10 hours of online didactic and hands-on training, respectively. Pre–post comparisons showed that there were statistically significant improvements in faculty participants' ability to interpret images ( p <0.001), perceived understanding of the capabilities and limitations of POCUS ( p= 0.003), comfort using POCUS to make clinical decisions ( p= 0.003), and perceptions regarding the extent to which POCUS can improve patient care ( p= 0.026). The next challenge for IM programs is to improve access to ultrasound machines and provide follow-up workshops to facilitate further development of skills and integration of POCUS into daily practice by general medicine faculty.